Improve product quantity of aromatase inhibitor from Nicotiana tabaccum by metabolic engineering techique - Amid, Azura; Jimat, Dzun Noraini (2010)
OBJECTIVES The objectives of this project are:  To increase amount of aromatase inhibitor from Nicotiana tabacum  To block sub-nicotine pathway in order to increase the amount of nicotine